AN ANALYSIS ON ANTISOCIAL PERSONALITY DISORDER OF KEVIN IN “WE NEED TO TALK ABOUT KEVIN MOVIE DIRECTED” BY LYNNE RAMSAY - Suhendar Suhendar (Journal of English Language and Literature (JELL), 2018)
The aim of this analysis is to know and understand the criteria, causes, influence, characters and moral messages of Kevin in Analysis on Antisocial Personality Disorder of Kevin in “We Need to talk about Kevin Movie Directed by Lynne Ramsay”. This method uses descriptive qualitative analysis. The analytical results obtained are: (1) Criteria of antisocial personality disorder of Kevin namely among the other things deceitfulness, irritability, aggressiveness, reckless, disregard for safety of his own self or for others and lack of remorse. (2) The causes of antisocial personality disorder on Kevin is less responsive (genetic) and neglect of family on Kevin (Environment). (3) Kevin’s behaviour influencing the others is posing of a threat and (4) Moral message that people should anticipate with antisocial personality disorder is that people should not hurt the person and should communicate with him very well. As a result, Kevin has the characters of aggressiveness, easily lying and can injure others without feeling any guilt.